LEGAL CERTIFICATION IN ELECTRONIC CREDIT AGREEMENT (Faculty of Law, Universitas Negeri Semarang, 2018)
Today's business development is very advanced. No longer developing only business that leads conventionally but also leads to technology-based business. The business of trade and services that lead to this technology also eventually also requires assistance from the financial services sector in the context of developing its business. Financial technology or better known as fintech is innovation in the field of financial services. Fintech is better known in recent years in the business world. This happens because technology evolves with the times. The development and evolution of this technology can make individuals today become easier in doing business. One service from Fintech that is currently popular is often also called Peer-to-Peer (P2P) Lending, or a company that brings lenders with loan seekers in one container, which financing or credit agreement is carried out with an online system and with the form of a standard agreement electronically. The financing or credit agreement is signed with an electronic signature and no stamp. This will cause problems if there is a default when the loan payment cannot be paid. What legal certainty can be given to creditors and debtors in the loan agreement. The research method used in this paper is a normative juridical legal research method. Where normative legal research is carried out by examining legislation and other literary materials.